2002
DOI: 10.1046/j.1461-9563.2002.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

A field experiment on the effectiveness of spiders and carabid beetles as biocontrol agents in soybean

Abstract: 1 Spiders and carabid beetles are abundant generalist predators that prey upon insect pests of soybean. A ®eld experiment was conducted to determine the impact of spiders and carabids on soybean yield. Prior to planting, three 7 3 7 m plots were fenced in order to reduce spider and carabid immigration. Carabids that emerged within the plots were not removed, but spiders that ballooned into these predatorreduction plots or that entered by climbing the fence were removed by pitfall trapping and searching the veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
5
0
3
Order By: Relevance
“…This study adds to the growing body of evidence that generalist predators have strong effects on prey, and is novel in demonstrating that these effects cascade down to increase plant biomass and yield. Trophic cascades are pervasive in terrestrial ecosystems (Schmitz et al 2000, , but see ), and have been demonstrated in agricultural systems, including vegetable (Snyder and Wise 1999, 2000, 2001), perennial (Cardinale et al 2003), and annual crops (Carter and Rypstra 1995, Colfer and Rosenheim 2001, Rypstra and Marshall 2005), although some studies fail to show significant impacts (e.g., Vichitbandha and Wise 2002). Our findings showed that strong top‐down control by lady beetles can completely release soybean plants from aphid pressure and restore plant biomass and yield.…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to the growing body of evidence that generalist predators have strong effects on prey, and is novel in demonstrating that these effects cascade down to increase plant biomass and yield. Trophic cascades are pervasive in terrestrial ecosystems (Schmitz et al 2000, , but see ), and have been demonstrated in agricultural systems, including vegetable (Snyder and Wise 1999, 2000, 2001), perennial (Cardinale et al 2003), and annual crops (Carter and Rypstra 1995, Colfer and Rosenheim 2001, Rypstra and Marshall 2005), although some studies fail to show significant impacts (e.g., Vichitbandha and Wise 2002). Our findings showed that strong top‐down control by lady beetles can completely release soybean plants from aphid pressure and restore plant biomass and yield.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that generalist arthropod predators choose to eat certain prey to balance their amino-acid requirements and therefore may be affected by previous feeding (Greenstone, 1979). While most ecological studies on spiders as potential biocontrol agents in agroecosystems have focused on Lycosidae, Linyphiidae, and Araenidae, much less is known about Thomisidae (Dean et al, 1987;Agnew and Smith, 1989;Lang et al, 1999;Symondson et al, 2002;Vichitbandha and Wise, 2002;Romero and Vasconcello-Neto, 2003;Harwood et al, 2004). In Michigan, Gardiner et al (2011) observed that the exotic coccinellids Coccinella septempunctata and Harmonia axyridis were the most abundant predators found in soybean field.…”
Section: Introductionmentioning
confidence: 99%
“…Las arañas atacan a sus presas con relación a la tasa de encuentro, y cuanto mayor es la densidad de una población presa (como ocurre en numerosos monocultivos), mayor es la proporción de ataques hacia dicha presa (Riechert & Gillespie 1983). Existen numerosas investigaciones que han demostrado que las arañas pueden ser importantes agentes de control biológico de especies plaga tales como áfidos, larvas de lepidópteros, ortópteros, homópteros, algunos coleópteros y pequeños dípteros en distintos agroecosistemas (Riechert & Lockley 1984, Nyffeler et al 1994b, Nyffeler & Sunderland 2003, Marc et al 1999, Vichitbandha & Wise 2002, Lang 2003.…”
unclassified